Cataloging correctly for kids an introduction to the tools - Intner, Sheila S.; Fountain, Joanna F.; Weihs, Jean Riddle; Association for Library Collections & Technical Services; IG Publishing (Chicago American Library Association, 2011)
It is a time of productive and exciting changes in the cataloging world, and cataloging for children is placed squarely in the middle of this upheaval, offering librarians working with kids a particular opportunity. This new fifth edition of the classic Cataloging Correctly for Kids points the way towards providing effective cataloging for materials intended for children and young adults. Based on guidelines issued by the Association for Library Collections and Technical Services (ALCTS), this handbook is a one-stop resource for librarians who organize information for children. Revisions include comprehensive updates on bibliographic description and subject access, A new chapter exploring cataloging for non-English-speaking and preliterate children, Guidance on when and how to move to RDA, the next generation of cataloging guidelines, With advice contributed by experienced, practicing librarians, the fifth edition of Cataloging Correctly for Kids offers a complete overview of the best methods for enabling children to find the information they want and need.
Guidelines for standardized cataloging for children / Joanna F. Fountain for the Association for Library Collections and Technical Services, Cataloging and Classification Section, Cataloging of Children's Materials Committee -- How children search / Lynne A. Jacobsen -- Cataloging correctly using AACR2 and MARC 21 / Deborah A. Fritz -- Copy cataloging correctly / Deborah A. Fritz -- Cataloging correctly (someday) using RDA / Deborah A. Fritz with Lynnette Fields -- Authority control and kids cataloging / Kay E. Lowell -- Using LC's children's subject headings in catalogs for children and young adults : why and how / Joanna F. Fountain -- Sears list of subject headings / Joseph Miller -- Dewey decimal classification / Julianne Beall -- Cataloging nonbook materials / Sheila S. Intner and Jean Weihs -- How the CIP program helps children's librarians / Joanna F. Fountain and Michele Zwierski -- Cataloging for kids in the academic library / Gabriele I. Kupitz -- Cataloging for non-English-speaking and pre-literate children / Pamela J. Newberg -- Automating the children's catalog / Judith Yurczyk -- Vendors of cataloging for children's materials / Pamela J. Newberg and Jennifer Allen.
Electronic reproduction.
Keywords: Cataloging of children's literature; Cataloging of children's literature -- United States; Electronic books